Erratum. (September 2013) - Unknown
The following article was published in the March 2013 issue of Behavior Modification and was inadvertently published again on OnlineFirst. The duplicate publication is hereby withdrawn. Below is the citation for the original publication. Schare, M.L. & Wyatt K.P. (2013). On the evolving nature of exposure therapy. Behavior Modification, 37, 243-256. (doi. 10.1177/01454455134774**21)